2020
DOI: 10.1177/0021955x20950224
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the forming and evolution process of cell structure in gas counter pressure assisted chemical foaming injection molded parts

Abstract: By using a standard stretch spline as the research object, the influence of gas counter pressure (GCP) technology on melt foaming behavior in chemical foaming injection molding (CFIM) process was investigated. Related experimental line for GCP assisted CFIM foam was designed, and the effect of GCP technology on melt flow front, spline surface quality and internal cell was studied. According to the results obtained from the experiment, two critical GCP pressures and one critical GCP holding time were innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…This is caused by gas penetration into the melt during the melt filling process [ 23 ]. However, Li et al [ 29 ] observed several pits caused by cell rupture and many gas marks on the melt front when not using GCP, although they used CBA foaming. There is a series of cells along the transition area between the skin and core layers of the part with a holding time of 10 s as shown in Figure 4 C1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is caused by gas penetration into the melt during the melt filling process [ 23 ]. However, Li et al [ 29 ] observed several pits caused by cell rupture and many gas marks on the melt front when not using GCP, although they used CBA foaming. There is a series of cells along the transition area between the skin and core layers of the part with a holding time of 10 s as shown in Figure 4 C1.…”
Section: Resultsmentioning
confidence: 99%
“…The surface roughness at the gate, mid, and flow end are 49.4, 47.37, and 45.69 μm, respectively, for microcellular injection-molding. The microcellular injection-molding has silver streaks, swirl marks, and blisters on the surface, which are caused by microcells on the melt front of the core section trapped by the mold wall (this is the fountain flow effect in the filling process), thus leading to the rough surface [ 29 , 35 ]. The gate has the highest surface roughness of the three positions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, the decomposition residues will cause frosting on the surface of the plastic part. 6 It is reported that "gas-counter" 7 and "core-back" 8 technologies were applied on the basis of the traditional CFIM process, which increases the equipment cost and makes the process control more complicated. Therefore, it is almost impossible to optimize the cellular structure by simply adding a new process or regulating the molding process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…There are two mainstream ways to improve the surface quality of foaming products: using gas counter pressure (GCP) technology [8][9][10][11][12] or reducing the cooling rate by increasing the mold temperature. 7,[13][14][15][16][17] Many researchers focused on using GCP technology to improve surface quality.…”
mentioning
confidence: 99%